Comparative study of tip cross-sections for efficient galloping energy harvesting - Yang, Yaowen (2013)
This letter presents a comparative study of different tip cross-sections for small scale wind energy harvesting based on galloping phenomenon. A prototype device is fabricated with a piezoelectric cantilever and a tip body with various cross-section profiles (square, rectangle, triangle, and D-shape) and tested in a wind tunnel. Experimental results demonstrate the superiority of the square-sectioned tip for the low cut-in wind speed of 2.5 m/s and the high peak power of 8.4 mW. An analytical model is established and verified by the experimental results. It is recommended that the square section should be used for small wind galloping energy harvesters.